Experimental estimation of emplacement depth of granitic dikes from the Sør RondaneMountains, East Antarctica - Oba, Takanobu; Shiraishi, Kazuyuki (National Institute of Polar Research, 1999)
P(論文) In order to estimate the depth of emplacement of the granitic dikes intruded into the granulites of the Sør Rondane Mountains, phase relations of the retrograde granulites adjacent to the dikes and the host granulites were experimentally determined in a temperature range of 600 to 900°C, under water pressures of 0.1-0.33 Gpa and oxygen fugacities of the FMQ and NNO buffers. The preliminary experimental results indicate that biotite from retrograde granulite is stable at pressures lower than 0.3 Gpa. The stability field of biotite in the gneisses suggests that the depth of emplacement of the granitic dikes from the northern central part of the mountains is similar to that of syenites from the southern central part of the mountains (T. OBA and K. SHIRAISHI; Proc. NIPR Symp. Antarct. Geosci., 8, 96, 1995) departmental bulletin paper